Understanding the genetics of APOE and TOMM40 and role of mitochondrial structure and function in clinical pharmacology of Alzheimer's disease. Issue 6 (3rd May 2016) - Roses, Allen; Sundseth, Scott; Saunders, Ann; Gottschalk, William; Burns, Dan; Lutz, Michael
Abstract: The methodology of Genome‐Wide Association Screening (GWAS) has been applied for more than a decade. Translation to clinical utility has been limited, especially in Alzheimer's Disease (AD). It has become standard practice in the analyses of more than two dozen AD GWAS studies to exclude the apolipoprotein E ( APOE ) region because of its extraordinary statistical support, unique thus far in complex human diseases. New genes associated with AD are proposed frequently based on SNPs associated with odds ratio (OR) < 1.2. Most of these SNPs are not located within the associated gene exons or introns but are located variable distances away. Often pathologic hypotheses for these genes are presented, with little or no experimental support. By eliminating the analyses of the APOE‐TOMM40 linkage disequilibrium region, the relationship and data of several genes that are co‐located in that LD region have been largely ignored. Early negative interpretations limited the interest of understanding the genetic data derived from GWAS, particularly regarding the TOMM40 gene. This commentary describes the history and problem(s) in interpretation of the genetic interrogation of the " APOE " region and provides insight into a metabolic mitochondrial basis for the etiology of AD using both APOE and TOMM40 genetics.